DEVELOPMENT AND ANALYSIS OF A MATHEMATICAL MODEL OF CARBON POLLUTION LEVEL ON KENYAN HIGHWAYS WITH HUGE EMBANKMENTS - Awino, John Otieno; Onyango, Thomas; Okelo, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
Carbon pollution on highways is attributed to major health problems experienced by those who stay along the highways. Most existing models developed by researchers have shown that CO which is the cause of many diseases suffered by those who stay close to highways. However, most researches have shown lack of mechanistic understanding of how roadside barriers affect pollutant transport and transformation on and near roadways, especially under different meteorological conditions and barrier properties, for example highway embankment. In this study we have therefore constructed a mathematical model incorporating embankment as a parameter. The black carbon concentration in the atmosphere along highways at different time scales will be simulated numerically using Finite Volume Method (FVM), with assumption that presence of embankment affects the physical parameters such as convection, Advection and diffusion.